From dream to action : imagination and (im)possible futures - Valério, Tatiana; Bastos, Ana Clara de Sousa Bittencourt; Tateo, Luca (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"The ubiquitous presence of imaginative work points at its importance among the higher mental functions. This collective volume discusses both the social relevance of imagination, that cannot be reduced to an inter-individual feature, and the cultural-historical conditions of imagining. The authors develop different theoretical and empirical works in which imagining, planning, anticipating, remembering and acting are put in relation with crucial moments of human existence, as early as birth and even after death. The proposal of this volume emerged during a "kitchen seminar" session at the III International Seminar of Cultural Psychology in Salvador da Bahia (Brazil, 2017). The debate revolved around the imaginative capability of human beings and the possibilities to investigate this phenomenon in a new key. The awareness that an innovative theoretical and empirical contribution was needed to the understanding of imaginative phenomena in everyday life led to the proposal of the book From Dream to Action: Imagination and (Im)Possible Futures. The book aims to talk to different audiences: psychologists, sociologists, artists, teachers and healthcare professionals, addressing a variety of life experiences - such as imagining alternative futures when facing a terminal illness, an adoption, a transplant waiting list, or the choice to give up your musical instrument - mobilize multiple dimensions of human psyche, from the basic emotions to the more sophisticated higher mental functions. The constant effort is to understand the psychological and sociocultural dynamics of each event, and to contribute to the understanding of human imagining in the area of semiotic-cultural psychology, dialoguing with contributions from all the human and social sciences."- Provided by publisher.
Keywords: Imagination.; Motivation (Psychology); Self-realization.; Self-actualization (Psychology); Psychology -- Creative Ability.; Cognition and cognitive psychology.; elektronické knihy; electronic books